(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The irrigation of the palm is provided by arterial arches (shallow and deep) that are made more frequently by the ulnar or radial arteries described as setting a classic pattern. Anatomical variations are described in shaping both arches, most often in the superficial palmar arch; may be the same complete or incomplete. The objective of this work is the anatomical description of the palmar arches, their different patterns and variations in conformation, and their clinical and surgical implications. A descriptive, observational and morphometric study of the arteries involved in the formation of the palmar arches was done in the Faculty of Medicine, University of Buenos Aires. One hundred1(00) cadaveric preparations fixed in formalin solution, of the Third Chair of Anatomy were used. A retrospective analysis of cases with lesions / s artery / main / s that make the palmar arches in the Emergency Hospital of Moron, between 2015-2016 s was also carried out. Most frequently the radial artery forms the deep palmar arch with the deep palmar branch of the ulnar artery. Superficial palmar arch is the most variable. It was complete in 56 % and the most common presentation (83 %) is one that is formed by the anastomosis of the ulnar artery and the superficial palmar branch of the radial artery. The rest of the anastomosis are between ulnar artery and median artery (9%), between deep branch of radial artery and ulnar artery (5 %); triple anastomosis between ulnar artery, median artery and superficial palmar branch of the radial artery (2 %), and anastomosis between the median artery and superficial palmar branch of the radial artery without participation of the ulnar artery (1 %). The rest of the sample (44 %) can be termed as incomplete. The B1a and B1b subtypes were the most found. Two cases, one entire section of the radial artery at the wrist and the other with complete section of ulnar artery with involvement of the ulnar nerve are described. It is essential to a proper understanding of the palmar arches for a suitable surgical approach to hand. The importance of the presence or absence, as well as different variations of palmar arterial arch lies in its clinical application as surgical starting point in the treatment of trauma and other diseases in which there is engagement of arteries.